2020
DOI: 10.1136/bmjsem-2019-000614
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of sports massage on performance and recovery: a systematic review and meta-analysis

Abstract: ObjectiveMassage is ubiquitous in elite sport and increasingly common at amateur level but the evidence base for this intervention has not been reviewed systematically. We therefore performed a systematic review and meta-analysis examining the effect of massage on measures of sporting performance and recovery.Design and eligibilityWe searched PubMed, MEDLINE and Cochrane to identify randomised studies that tested the effect of manual massage on measures of sporting performance and/or recovery. We performed sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 48 publications
3
72
0
7
Order By: Relevance
“…This is similar to previous studies [19,41], who report that ROM has not recovered for short term and does not have any substantial effect on it. These findings, in turn, are also similar to previous studies [13,14], where both treatments show no beneficial effects on muscle function. Therefore, increasing blood flow to provide oxygen and other substances needed for the damaged tissue to regenerate is clearly not adequately effective by massage and FR.…”
Section: Discussion Conclusion and Recommendationsupporting
confidence: 92%
See 2 more Smart Citations
“…This is similar to previous studies [19,41], who report that ROM has not recovered for short term and does not have any substantial effect on it. These findings, in turn, are also similar to previous studies [13,14], where both treatments show no beneficial effects on muscle function. Therefore, increasing blood flow to provide oxygen and other substances needed for the damaged tissue to regenerate is clearly not adequately effective by massage and FR.…”
Section: Discussion Conclusion and Recommendationsupporting
confidence: 92%
“…The consequence of previous studies [13][14][15] showed that there was no significant effect on the elbow flexion range of motion of SM and FR that prove ROM has not recovered for short term and does not have any substantial effect on it. They found that where both treatments show no beneficial effects on muscle function.…”
Section: Research Backgroundmentioning
confidence: 83%
See 1 more Smart Citation
“…MT is ubiquitous in elite sports and is becoming increasingly common at the amateur level, but the evidence base for this intervention has not been systematically reviewed. A recent study by Davis et al have emphasized on the difficulty of standardizing treatment but suggested a possible improvement in flexibility and DOMS [ 42 ]. It should be noted that the differences found between the treated and untreated leg support the use of these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Dengan melakukan gosokan yang diberikan dipermukaan kulit mempercepat aliran darah yang mengakibatkan pertukaran oksigen dan karbondioksida serta darah di pembuluh darah yang akan mempercepat keluarnya asam laktat. Massage juga secara signifikan dapat mengurangi kelelahan otot (Davis, Alabed, & Chico, 2020).…”
Section: Pembahasanunclassified